Peptides at the tRNA binding site of the crystallizable monomeric form of E. coli methionyl-tRNA synthetase. - Schulman, L H (1987)
A protein affinity labeling derivative of E. coli tRNA(fMet) carrying lysine-reactive cross-linking groups has been covalently coupled to monomeric trypsin-modified E. coli methionyl-tRNA synthetase. The cross-linked tRNA-synthetase complex has been isolated by gel filtration, digested with trypsin, and the tRNA-bound peptides separated from the bulk of the free tryptic peptides by anion exchange chromatography. The bound peptides were released from the tRNA by cleavage of the disulfide bond of the cross-linker and purified by reverse-phase high-pressure liquid chromatography, yielding three major peptides. These peptides were found to cochromatograph with three peptides of known sequence previously cross-linked to native methionyl-tRNA synthetase through lysine residues 402, 439 and 465. These results show that identical lysine residues are in close proximity to tRNA(fMet) bound to native dimeric methionyl-tRNA synthetase and to the crystallizable monomeric form of the enzyme, and indicate that cross-linking to the dimeric protein occurs on the occupied subunit of the 1:1 tRNA-synthetase complex.